PENGARUH PENERAPAN PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR EKONOMI KELAS XI IPS SMA TRI BHAKTI PEKANBARU - Yundha Ningrum Rizky Utomo; Gimin Gimin; Sumarno Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research aimed to know the influence of Scientific Approach curriculum 2013 assignment student’s learning on internasional trade. This research was conducted at SMA Tri Bhakti Pekanbaru academic year 2017/2018. The research method used is quasi experiment. Sampling with saturated sampling. The sample of the study were 32 students for the experimental class were 32 students. The research instrument used is question test which is in the form of multiple choice as much as 20 questions and notes in the form of observation sheet of student activity of affective and psychomotor aspects. Analysis of data of both groups using t-test obtained 0,000 at significant level p <0.000. This indicates that there is an influence of the application of scientific approach to economic learning outcomes on international trade materialKeywords: Scientific Approach, learning Achievement